2020
DOI: 10.3233/jad-191261
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid YKL-40 and Neurogranin in Familial Alzheimer’s Disease: A Pilot Study

Abstract: Background: YKL-40 and neurogranin are promising additional cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease (AD) which reflect different underlying disease mechanisms. Objective: To compare the levels of CSF YKL-40 and neurogranin between asymptomatic carriers of familial AD (FAD) mutations (MC) and non-carriers (NC) from the same families. Another objective was to assess changes in YKL-40 and neurogranin, from the presymptomatic to clinical phase of FAD. Methods: YKL-40 and neurogranin, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
4
8
0
Order By: Relevance
“…Gantenerumab and solanezumab had no effect on YKL-40 compared with placebo. Although increased YKL-40 level has been proposed to precede amyloid plaques, studies in sAD and DIAD have found no correlation with CSF Aβ42, ultimately leaving the treatment-related changes in YKL-40 levels a subject of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Gantenerumab and solanezumab had no effect on YKL-40 compared with placebo. Although increased YKL-40 level has been proposed to precede amyloid plaques, studies in sAD and DIAD have found no correlation with CSF Aβ42, ultimately leaving the treatment-related changes in YKL-40 levels a subject of future research.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized clinical examination included somatic, neurological, and psychiatric status, often an interview with a close informant, cognitive screening (MMSE) [ 12 ], cognitive assessment, Magnetic imaging, electric encephalography, and biochemical assessments of urine, blood, Cerebrospinal fluid markers (Abeta, total tau and phosphorylated tau), and fibroblast. Studies on non-cognitive outcomes have been reported elsewhere [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, CSF YKL-40 levels may be associated with the progression of the disease as it increased longitudinally in mild cognitive impairment and Alzheimer's disease patients but not in persons with normal cognitive function [153] (Table 2). In a recent pilot study, longitudinal records demonstrated an elevation in CSF YKL-40 levels in mild cognitive impairment patients as they approach symptomatic Alzheimer's disease [191]. These observations were confirmed in a study of the ADNI cohort, where, longitudinally, there was an elevation of CSF YKL-40 levels in all the groups over the mean followup time of 4 years, although the change in the biomarker was significant only in mild cognitive-impaired Aβ-positive patients [190].…”
Section: Cerebrospinal Fluid Chitinase-3-like Proteinmentioning
confidence: 99%